2013
DOI: 10.1111/1756-185x.12024
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile of benign joint hypermobility syndrome from a tertiary care military hospital in India

Abstract: BJHS is often under-recognized in clinical practice and is usually missed because of a lack of awareness. A high index of clinical suspicion to diagnose this entity is essential due to its associated morbidities, especially among those exposed to strenuous physical activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 24 publications
(26 reference statements)
1
13
0
Order By: Relevance
“…Receiving a correct diagnosis is necessary in order to access appropriate care pathways, for example, referral for physiotherapy for EDS-HT rather than for an acute single joint problem 84. A study conducted among military personnel found misdiagnosis of EDS-HT has a disabling impact on military personnel with EDS-HT who are exposed to strenuous physical activities 85. Significant neuromuscular and motor development problems have been found among a pediatric population, and delay in diagnosis resulted in poor control of pain and disruption of normal home life, schooling, and physical activities 64.…”
Section: General Remarksmentioning
confidence: 99%
“…Receiving a correct diagnosis is necessary in order to access appropriate care pathways, for example, referral for physiotherapy for EDS-HT rather than for an acute single joint problem 84. A study conducted among military personnel found misdiagnosis of EDS-HT has a disabling impact on military personnel with EDS-HT who are exposed to strenuous physical activities 85. Significant neuromuscular and motor development problems have been found among a pediatric population, and delay in diagnosis resulted in poor control of pain and disruption of normal home life, schooling, and physical activities 64.…”
Section: General Remarksmentioning
confidence: 99%
“…Need to consider even when presenting with non-specific MSK symptoms. The ‘lateral head tilt sign’ was an incidental finding in 10%, could be a leading clue Martinez, et al (2021) [ 25 ] ANS/Cardiology: dysautonomia, mitral valve prolapse (0% vs 3.6% vs 25.5%), aortic root dilation (0% vs 0% vs 6.1%) Dermatology: unusually soft or velvety skin (27.3% vs 67.9% vs 79.6%), mild hyperextensibility skin (31.8% vs 50% vs 51%), unexplained striae (27.3% vs 28.6% vs 59.2%), bilateral piezogenic papules (36.4% vs 39.3% vs 73.5%), atrophic scarring (13.6% vs 35.7% vs 55.1%) Gastroenterology: lump in throat, difficulty swallowing, nausea, vomiting, chest pain, intolerance of several foods, abdominal fullness, abdominal bloating, feeling of abdominal distension, abdominal pain, bowel noises, stools very rarely, frequent changing of stool consistency, hard or lumpy stools, straining during bowel movement, passage of mucous, feeling of incomplete evacuation, recurrent/multiple abdominal hernias (13.6% vs 7.1% vs 11.2%) Gynaecology: prolapse (pelvis, rectal, uterine) (0% vs 3.6% vs 15.3%) MSK/Orthopaedics: MSK/CWP (31.2% vs 89.3% vs 92.9%), joint dislocation/instability (9.1% vs 17.9% vs 38.8%), arachnodactyly (9.1% vs 28.6% vs 50%), arm span-to-height ratio (0% vs 3.6% vs 14.3%) Orthodontics: dental crowding/high narrow palate (18.2% vs 5.6% vs 69.4%) Miscellaneous: fatigue, daytime sleepiness Negative affect: fear of movement Miscellaneous: fatigue Hobbies/daily activities: fatigue affects activities HSD/hEDS groups had significant impairment of health-related QoL, complaints of generalised pain and self-reported symptoms including fear of movement, fatigue, daytime sleepiness, gastrointestinal concerns and dysautonomia Folci & Capsoni (2016) [ 26 ] Dermatology: thin skin, elastic skin Gastroenterology: abdominal discomfort, alternating bowel MSK/Orthopaedics: recurrent sprains, joint pain, pain in the TMJ, dislocate TMJ, twist and stretch thoracic-lumbar spine, axial and peripheral joint mobility, widespread joint hypermobility, extra-range mobility (knees, elbows, fingers) Rheumatology: generalised arthralgia, myalgia, diffuse arthralgia (shoulders, ankles, wrists, knees) Urology: difficult urination, dysuria, pollakiuria Miscellaneous: persistent fatigue, tendonitis (wrists and ankles), lower limb paraesthesia, sleep disturbance, weight gain, chewing problems Cognitive: poor concentration Mood disorder: depressive mood Negative affect: frustration Miscellaneous: fatigue, sleep disturbance, pain Daily living: bedridden, change in lifestyle, heavy impact on life Hobbies/daily activities: ceased physical activities Clinical complexity and the multidisciplinary importance of an unexpectedly common disease that still tends to be under-recognised. Early diagnosis is essential to avoid long and unnecessary diagnostic paths.…”
Section: Resultsmentioning
confidence: 99%
“…Another [ 24 ] described how involvement from a specialist hypermobility physiotherapist improved their understanding of their own bodies via a two-way learning process which in turn motivated these individuals to engage in appropriate self-management of their condition. Within assessments of EDS/HSD, individuals are subject to dermatological evaluation [ 25 ], this is because skin hyperextensibility is as common as MSK symptoms [ 9 , 26 ] with additional dermatological symptoms identified such as, thin skin [ 27 29 ] and abnormal scarring [ 9 , 19 ]. A significant number of participants in one study [ 19 ] suggested that the MSK and skin symptoms began as early as childhood yet despite these widely recognised and long-standing symptoms, the condition is often underdiagnosed [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that benign hypermobility syndrome is common in the Indian population[ 5 ] but it is unrecognized and less often reported. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%